Haiti : Staff Report for the 2001 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This 2001 Article IV Consultation highlights that Haiti's performance under the Staff-Monitored Program (SMP) during FY2000/01 was weak. Real GDP is estimated to have declined by about 2 percent, reflecting tight monetary conditions and the negative expectations raised by the continuing high fiscal imbalance and central bank financing; inflation remained broadly unchanged at about 16 percent during most of the year. Tight monetary conditions and crowding out by the public sector combined with the weak economy and continuing political uncertainty all contributed to a sharp decline in credit to the private sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet